2002
DOI: 10.1053/eupc.2002.0256
|View full text |Cite
|
Sign up to set email alerts
|

The electromechanical effects of pacing at different sites within the right atrium

Abstract: High right atrial free wall or the right atrial appendage pacing, when compared with sinus rhythm, is significantly detrimental to atrial electromechanical function. There is, however, no demonstrable difference between the two sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…RAA pacing was detrimental to cardiac electromechanical function when compared to sinus rhythm [20]. Since no measurements during sinus rhythm were performed in our study (because of substantial bradycardia), we cannot rule out the possibility that what we observed was not an advantageous effect of BiA but only a correction of an unfavorable effect of RAA pacing.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…RAA pacing was detrimental to cardiac electromechanical function when compared to sinus rhythm [20]. Since no measurements during sinus rhythm were performed in our study (because of substantial bradycardia), we cannot rule out the possibility that what we observed was not an advantageous effect of BiA but only a correction of an unfavorable effect of RAA pacing.…”
Section: Discussionmentioning
confidence: 84%
“…More synchronous LA segment contraction during BiA in comparison to single site (RAA or CS) pacing might explain this observation [17, 18]. A positive influence of BiA pacing on global systolic LA function was observed in the stunned atrium after cardioversion of persistent AF [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mode switching is another example of an over utilized algorithm that can have negative patient consequences. Mode switch studies have shown that inappropriate mode switching occurs anywhere from 9% to 38% of the time 42–56 . These occurrences can be especially detrimental to CRT patients where therapy delivery will be inappropriately withheld.…”
Section: Cardiac Rhythm Management Device Selection Position Statementmentioning
confidence: 99%
“…Belham and colleagues 22 demonstrated that, regardless of the location of pacing in the right atrium, pacing itself was detrimental to atrial electromechanical function in comparison with sinus rhythm. However, Quintana et al 23 demonstrated that short-term atrial pacing improved LAMF.…”
Section: Patient Presentation (Continued)mentioning
confidence: 99%